1515 A Survey on The Perceived Effect of Background Music on Intra-Operative Stress, Anxiety and Surgical Task Load On the Operating Surgeon. (12th October 2021) - Pearson, L; Narayanan, A; Fisher, J; Khashram, M
Abstract: Introduction: Music is commonly played in operating theatres throughout the world though its use remains controversial. There is growing literature supporting the notion that playing background music can improve a surgeon's task performance and reduce performance stress. We present findings from our survey of surgeons about their perceptions of the effect of intra-operative music on their stress levels. Method: Surgeons and registrars from three different specialties – general, vascular, and paediatric surgery – in a single tertiary centre were surveyed on their views on the effect of music in theatre. Two instruments were used to assess parameters of stress: the modified 6-point state trait anxiety inventory (STAI-6) and the surgical task load index (SURG-TLX). Results: There were 35 respondents across the three surgical specialties (78% response rate). Pop and "easy listening" were the most popular genres. A majority felt music improved their temperament (75%) and perceived stress (63%). 59% of respondents reported no to low perceived anxiety with music, compared with 31% reporting moderate and 9% high anxiety based on STAI-6 parameters. Regarding SURG-TLX parameters and music, respondents overall perceived feeling less anxious, rushed and mentally fatigued though more distracted. Conclusions: Music is generally thought to have positive subjective effects on the theatre environment with regards to anxiety levels, temperament, perceived stress, and parameters within the surgical task load index. This is counterbalanced by a smaller group of respondents who felt that music can impair communication and increase distraction within theatre. Music used appropriately may reduce perceptions of stress in theatre.